Strategic Leadership of School Administrators and Social Responsibility - Saninta, Wanida; Vadasatto, Phra Honda (Journal of Graduate MCU KhonKaen Campus, 2022)
The administrators of the private schools are considered to be the people who are really important and leaders in driving the schools in the management of the schools to be successful in the midst of a globalized society which has progressed in industrial technology Fast communication without borders Society, economy and environment are rapidly changing in today's society. As a result, the way of life of the people of the world's citizens is more competitive for survival, seeing only personal interests without considering participation. lack of morality which cause various problems followed by many such as child labor problems crime problem Corruption problem And it is especially important to cause problems with the quality of education being reduced or the education is not up to standard. The problems as mentioned above, educational institution administrators or educational institution leaders Therefore, it must be realized that there is a role to focus on social responsibility known as CSR (corporate social responsibility) to help solve economic, social and environmental problems, especially the quality of education. School administrators must be confident in their studies. Develop yourself to be a leader with strategic leadership. Change management strategies by using strategic leadership to combine with social responsibility of educational institutions. as a strategy for socially responsible management of educational institutions. Therefore, it can motivate and motivate people in schools and communities to work together to raise awareness of the importance of social responsibility. Affects the development of economic, social quality, educational quality, and people in the community are satisfied with the quality of educational institutions. Build faith, trust, create a good image for educational institutions that are sustainable forever